Changes in agrarian structure in the EU during the period 2010-2016 in terms of typological groups of countries - Jadwiga Bożek; Czesław Nowak; Monika Zioło (Agricultural Economics (AGRICECON), 2020)
The paper presents the changes in the spatial structure of agricultural holdings in the European Union between 2010 and 2016 from the perspective of typological groups of countries. The research was conducted based on Eurostat data. The holdings were divided into the following groups: up to 5 ha of agricultural land (AL), 5-20 ha, 20-50 ha, and over 50 ha. Based on the fuzzy classification method, 4 typological groups of countries with a similar spatial structure of holdings were distinguished. The intergroup diversity is high. The dynamics of changes in the number of holdings in particular countries per typological group was presented. A downward trend in the total number of holdings and smallholdings was observed, in particular in countries characterised by a fragmented structure of holdings. In these countries, an upward trend in the number of holdings of 20-50 ha and over 50 ha was noted. Between 2010 and 2016, the structure and composition of typological groups changed. There were also slight changes (in different directions) in the structural distance between the groups.